MENTAL HEALTH DEVELOPMENT OF CHILDREN THROUGH AN ISLAMIC GROUP GUIDANCE APPROACH AT THE ACEH SEPAKAT DARUL AITAM ORPHAN CARE FOUNDATION, MEDAN - Tamara Dilla Tiffani; Dika Sahputra (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
Children’s mental health is an important aspect in personality development and social life. Children living in orphanages are vulnerable to emotional and psychological problems due to lack of attention and affection from their families, so appropriate guidance efforts are needed through an Islamic group guidance approach. This study aims to determine the effect of fostering children’s mental health through an Islamic group guidance approach at the Yayasan Penyantunan Yatim Piatu Aceh Sepakat Darul Aitam Medan. This study was conducted using a quantitative method with a pre-experimental research type with a pretest-posttest one group design. The selection of research subjects used purposive sampling totaling 12 children. Data analysis used the One Sample T-Test with the SPSS 25 program. The research findings indicate that the Islamic group guidance approach is effective in improving children’s mental health. This can be seen from the differences in children in the experimental group in the pretest and posttest with a significance of 0.000 or a probability below alpha (0.000 <0.05). Based on the above findings, it can be concluded that the Islamic group guidance approach is effective in improving children’s mental health at the Yayasan Penyantunan Yatim Piatu Aceh Sepakat Darul Aitam Medan.